Mekanisme Penggunaan Tenaga Kerja Asing Di Indonesia Berdasarkan Peraturan Presiden Nomor 20 Tahun 2018 Tentang Penggunaan Tenaga Kerja Asing - Karvin Fadila; Abdullah Sulaiman (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.The background of this research is based on the existence of mechanisms that are often violated and there are several articles in this presidential regulation that cause legal uncertainty. Not only that, many of them do not meet the terms and conditions that have been regulated by legislation, so that many foreign workers do not meet expectations. This study examines the laws and regulations especially Presidential Regulation Number 20 Year 2018 and relates cases that often occur to strengthen this research. The approach used is normative by using primary legal materials consisting of Law Number 13 of 2003 concerning Labor, Presidential Regulation Number 20 of 2018 concerning Use of Foreign Workers. The results showed that the Republican foreign labor mechanism based on Presidential Regulation Number 20 Year 2018 on the Use of Foreign Workers whose articles violated the rules above and caused legal uncertainty, causing violations in carrying out the mandate of the law and the need for a review of the regulations this president so that there are no articles that conflict with the rules above.Keywords: Foreign Workers, Presidential Regulation